Dynamics and timescales of mafic–silicic magma interactions at Soufrière Hills Volcano, Montserrat - Didonna, Rosa (2022)
Mafic magma intrusions into silica-rich magmatic reservoirs are commonly proposed to drive the eruptions of andesitic hybrid magmas that characterise many arc volcanoes. However, interactions between contrasting magmas involve large gradients of physical and chemical properties that change over time, and the details of such processes have proven difficult to constrain. In this paper we investigate the dynamics of magma mingling and mixing using chemical and textural zoning patterns recorded in plagioclase crystals from the February 2010 eruption at Soufrière Hills Volcano, Montserrat. This eruption is considered a classic example of interactions between the andesite magma that constitutes the bulk of the erupted volume and the basaltic andesite that occurs as enclaves. We find that plagioclase crystals are characterised by two well-defined zones that record mafic–silicic magma interaction: a crystal interior, often identified by a patchy, dusty and oscillatory zoning, and an overgrowth zone (rim) of a different composition. We use the anorthite and Mg contents to track the thermal and compositional changes experienced by the crystals over time. Our results reveal that the crystal rims formed a few hours to days prior to eruption, during co-eruptive magmatic interactions. The interaction between the two magmas with contrasting rheology is likely increased by a narrowing conduit geometry towards the surface, which facilitates convection and additional interface contact of the two magmas. Our findings shed new light on the nature and timing of magmatic interactions driving the final eruptive phase at Soufrière Hills Volcano and help to propose an interpretative framework of the monitoring signals.